Pemetaan Kualitas Tanah pada Lahan Kebun Campuran dengan Geography Information System (GIS) di Kecamatan Tegallalang, Kabupaten Gianyar - SAIFULLOH, MOH; SARDIANA, I KETUT; SUPADMA, A.A. NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.3, Juli 2017, 2017)
The Mapping of Soil Quality Under Mixed Dry Land Farming Using Geography Information System (GIS) at Tegallalang, Gianyar Regency Mapping of soil quality undermixed dry land farming area using GIS was held in Tegallalang, Gianyar Regency on October 2016 – January 2017. This research implementing exploratory method on the purposive land use followed by laboratory soil analysis. Soil samples were randomly taken on each homogeneous land units on the map developed by overlaying slope, soil type, and land use maps. The following soil quality indicators as the minimum data set (MDS) were measured: soil bulk density, porosity, field capacity water content, texture, pH, C-Organic, CEC, base saturation, nutrients (N, P and K), and C-biomass. The values of soil quality were mapping using QGIS 2.18.0 and refer to land management direction. The results showed that the soil quality in the research area considered being good and medium level. The good soil quality present on land units laid down on the wavy slope had different land cover vegetation, different land management systems (fertilizer, without fertilizer, soil tillage and without soil tillage). The medium soil quality was including land units that present on steep slope, had different land cover vegetation without land managements. The limiting factors of soil quality were texture, C-Organic, CEC, base saturation, N and C-biomass. It was recommended to tillage the soil using hoe and applying organic fertilizer, Urea, and dolomite on the farming area.